The Role of Financial Intermediaries in the Internationalization of Capital Markets in Kenya: A Study of stock brokers in Kenya - Arasa, Robert; Mwaniki, Monicah; Kaihula, Prudensia (Journal of Economics and Behavioral Studies, 2015)
Financial intermediaries continue to play a big role in the internationalization of capital markets. In Kenya all transactions in the Nairobi Securities Exchange must be carried out by an authorized stock broker. This study covered the stockbrokers and their role in the internationalization of capital markets within Kenya. The study adopted a descriptive survey. Population of interest comprised of 19 stockbrokerage firms licensed to operate at the Nairobi Securities Exchange (NSE). The study findings indicate that stock brokers contribute to the internationalization of capital markets through their roles in facilitating cross-listing, offshoring and foreign investor by aiding in sourcing for investment opportunities, provision of relevant information and transaction facilitation. Study findings further reveals that the government issues, lack of awareness and knowledge on innovative strategies, adequate financial resources, availability of adequate infrastructure and trading costs affects stock brokers role in the internationalization of capital markets. The study recommends that the government and policy makers should direct efforts towards addressing the various bottlenecks that hinder the effectiveness of the stock brokers in the internationalization of capital markets in Kenya. Further, towards realizing efficiency and effectiveness these firms need to embrace technology and innovation.
Keywords: Stock brokers; Capital markets; Internationalization; Cross-listing; Foreign investment; Off-shoring